Ko te Tika, ko te Pono, ko te Aroha: Exploring Māori values in the university - Stewart, Georgina; Smith, Valance; Diamond, Piki; Paul, Nova; Hogg, Robert (Te Kaharoa, 2021)
This research is offered as a koha (contribution) to the ongoing debates within the university where all co-authors work as academic staff, Auckland University of Technology (AUT) in Auckland, Aotearoa New Zealand. We set out to critically investigate three key Māori words, tika, pono, aroha, and the results of their adoption as ‘university values’ by AUT. In the sections below, we synopsise and synthesise scholarly literature from a critical Māori perspective, informed by collective lived experience, including our experiences of being Māori academics, working at AUT. This research offers an internal critique of our employer university and is therefore an exercise in academic freedom and a form of activist research, as is consistent with the political nature of Kaupapa Māori approaches. While this article restricts itself to one university, the conundrum of using Māori knowledge in educational and other contemporary social institutions is topical across the nation. The key question we investigate is: Are these three words, tika, pono, aroha, being used by AUT in ways consistent with their Māori meanings?